2021
DOI: 10.3389/fcell.2021.670711
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine RNA Modification in Inflammation: Roles, Mechanisms, and Applications

Abstract: N6-methyladenosine (m6A) is the most prevalent internal mRNA modification. m6A can be installed by the methyltransferase complex and removed by demethylases, which are involved in regulating post-transcriptional expression of target genes. RNA methylation is linked to various inflammatory states, including autoimmunity, infection, metabolic disease, cancer, neurodegenerative diseases, heart diseases, and bone diseases. However, systematic knowledge of the relationship between m6A modification and inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 137 publications
0
48
0
Order By: Relevance
“…In recent years, a large number of studies have focused on the role of RNA modifications in regulating inflammation and anti-inflammatory gene expression. Among them, m6A modification may affect the states of various inflammatory diseases through a variety of mechanisms ( 38 ). For example, studies showed that m6A binding protein YTHDF2 could regulate the stability of inflammatory gene mRNA transcripts and participate in the regulation of lipopolysaccharide (LPS)-induced inflammation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies have focused on the role of RNA modifications in regulating inflammation and anti-inflammatory gene expression. Among them, m6A modification may affect the states of various inflammatory diseases through a variety of mechanisms ( 38 ). For example, studies showed that m6A binding protein YTHDF2 could regulate the stability of inflammatory gene mRNA transcripts and participate in the regulation of lipopolysaccharide (LPS)-induced inflammation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed significant hypermethylation in end-stage tissue from ALS patients compared to age-matched controls; although we do not believe age is responsible for the observed RNA hypermethylation, other factors may be playing a part. Since astrocytosis and microgliosis are common features of ALS as well as other neurodegenerative diseases, it is possible that much of the observed RNA hypermethylation arises not because of a primary disease mechanism, but instead because of secondary neuroinflammation 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Since astrocytosis and microgliosis are common features of ALS as well as other neurodegenerative diseases, it is possible that much of the observed RNA hypermethylation arises not because of a primary disease mechanism, but instead because of secondary neuroinflammation 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alterations in RNA m 6 A methylation status can lead to cell dysfunction and disease [ 12 ]. Recent studies have revealed that the m 6 A modification not only has a strong and intricate relationship with cardiovascular disease but may regulate also the inflammatory response arising during different physiopathological conditions [ 13 , 14 ]. Although the clinical significance of m 6 A profiling in sepsis patients has been recently suggested [ 11 ], there is a clear need for studies addressing the specific m 6 A alterations occurring in tissues and organs affected by sepsis.…”
Section: Discussionmentioning
confidence: 99%